Acute Toxicity of Ochratoxins A and B in Chicks - Peckham, John C. (Appl Microbiol, 1971)
Ochratoxins A and B were given to 1-day-old Babcock B-300 cockerels to evaluate acute toxic effects. Two trials with ochratoxin A gave 7-day oral median lethal dose estimates of 116 μg (3.3 mg/kg) and 135 μg (3.9 mg/kg) per chick. Chicks given daily oral doses of 100 μg of ochratoxin A died on the second day. Single subcutaneous doses of 400 μg of ochratoxin A were also lethal. The 7-day oral median lethal dose of B was estimated at 1,890 μg (54 mg/kg) per chick. Chicks given oral doses of 100 μg of ochratoxin B daily for 10 days survived. Sublethal doses of both ochratoxins A and B resulted in growth suppression which was proportional to the amount of ochratoxin given. Visceral gout was the principal gross finding. Microscopic examinations revealed acute nephrosis, hepatic degeneration or focal necrosis, and enteritis. Suppression of hematopoiesis in the bone marrow and depletion of lymphoid elements from the spleen and bursa of Fabricius were frequently seen. Both ochratoxins appeared to have similar pathological effects. This is the first report on the toxicity of ochratoxin B.